EBF1, MYO6 and CALR expression levels predict therapeutic response in diffuse large B-cell lymphomas - Turdo, Alice; Gaggianesi, Miriam; D’Accardo, Caterina; Porcelli, Gaetana; Bella, Sebastiano Di; Cricchio, Dario; Pillitteri, Irene; Porcasi, Rossana; Lo Iacono, Melania; Verona, Francesco; Modica, Chiara; Roozafzay, Narges; et al. (Frontiers in Immunology, 2023)
Diffuse large B-cell lymphoma (DLBCL) is a hematological malignancy representing one-third of non-Hodgkin's lymphoma cases. Notwithstanding immunotherapy in combination with chemotherapy (R-CHOP) is an effective therapeutic approach for DLBCL, a subset of patients encounters treatment resistance, leading to low survival rates.Thus, there is an urgent need to identify predictive biomarkers for DLBCL including the elderly population, which represents the fastest-growing segment of the population in Western countries.Gene expression profiles of n=414 DLBCL biopsies were retrieved from the public dataset GSE10846.Differentially expressed genes (DEGs) (fold change >1.4, p-value <0.05, n=387) have been clustered in responder and non-responder patient cohorts. An enrichment analysis has been performed on the top 30 up-regulated genes of responder and non-responder patients to identify the signatures involved in gene ontology (MSigDB).The more significantly up-regulated DEGs have been validated in our independent collection of formalin-fixed paraffin-embedded (FFPE) biopsy samples of elderly DLBCL patients, treated with R-CHOP as first-line therapy.From the analysis of two independent cohorts of DLBCL patients emerged a gene signature able to predict the response to R-CHOP therapy. In detail, expression levels of EBF1, MYO6, CALR are associated with a significant worse overall survival.These results pave the way for a novel characterization of DLBCL biomarkers, aiding the stratification of responder versus non-responder patients.